Grade Six Pupils’ Level of Screen Dependency and Its Implication to Learners’ Academic Performance in Kabayan District, Benguet - Tubal, Lorenza (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study aimed to determine the level of screen dependency among Grade 6 learners and its relationship to their academic performance during modular distance learning in Barangay Ballay and Barangay Tawangan, Kabayan, Benguet. Anchored on the concept of screen dependency disorder and its behavioral and academic implications, the study employed a descriptive-correlational research design. Data were collected using an adapted survey questionnaire (Jennifer, 2012) and respondents’ Grade Point Average (GPA), involving 83 Grade 6 pupils aged 11–12 years from four public schools. Descriptive and inferential statistics, including frequency, percentage, mean, t-test, ANOVA, and Pearson correlation, were utilized. Findings revealed that learners exhibited very low screen dependency across cellphones, television, video games, and the internet, attributed to parental guidance, limited gadget ownership, and unstable internet connectivity. Despite this, results showed that screen dependency has a slight but significant relationship with academic performance, indicating that increased exposure to digital screens can influence learners’ achievement. However, learners maintained a very satisfactory academic performance and demonstrated the ability to manage their screen use effectively without major negative effects on their learning, health, and behavior. These findings are consistent with prior studies emphasizing the link between technology use and academic outcomes (Azizi et al., 2019). The study recommends continuous monitoring, awareness programs, and further research to sustain low dependency levels and support academic success. This study supports Sustainable Development Goal 4 (Quality Education) by promoting effective learning conditions and responsible use of technology in education. It contributes to social sustainability by guiding educators and communities in fostering balanced digital habits and improving learners’ academic performance through informed interventions.